2022
DOI: 10.1155/2022/6205757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Etomidate-Ketamine Anesthesia on Perioperative Electrocardiogram and Postoperative Cognitive Dysfunction of Elderly Patients with Rheumatic Heart Valve Disease Undergoing Heart Valve Replacement

Abstract: Objective. To explore the effect of combined etomidate-ketamine anesthesia on perioperative electrocardiogram (ECG) and postoperative cognitive dysfunction (POCD) of elderly patients with rheumatic heart valve disease (RHVD) undergoing heart valve replacement. Methods. The data of 100 elderly RHVD patients treated in our hospital from May 2019 to May 2020 were selected for the retrospective analysis, and by adopting the double-blind method, the patients were divided into the ketamine group (n = 50) and the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In an RCT that included 100 participants, it was observed that older adults who received a single dose of ketamine during heart valve replacement surgery had a 20% incidence of POCD, which was significantly lower compared to the combined etomidate–ketamine group that had a 6% incidence. 42 In another RCT involving 182 patients, it was found that haloperidol and ketamine as individual treatments did not demonstrate a superior effect on the incidence of POCD compared with the control group (15.6% and 21.3% versus 13.6%); however, the combination group, which received both haloperidol and ketamine, exhibited a lower incidence of POCD compared to the control group (6.6% versus 13.6%). 24 Further research is needed to confirm the efficacy and safety of such combinations in preventing POCD.…”
Section: Discussionmentioning
confidence: 96%
“…In an RCT that included 100 participants, it was observed that older adults who received a single dose of ketamine during heart valve replacement surgery had a 20% incidence of POCD, which was significantly lower compared to the combined etomidate–ketamine group that had a 6% incidence. 42 In another RCT involving 182 patients, it was found that haloperidol and ketamine as individual treatments did not demonstrate a superior effect on the incidence of POCD compared with the control group (15.6% and 21.3% versus 13.6%); however, the combination group, which received both haloperidol and ketamine, exhibited a lower incidence of POCD compared to the control group (6.6% versus 13.6%). 24 Further research is needed to confirm the efficacy and safety of such combinations in preventing POCD.…”
Section: Discussionmentioning
confidence: 96%